2019
DOI: 10.1093/nargab/lqz008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structural variability of topologically associated domains as revealed by Hi-C

Abstract: Three-dimensional chromosome structure plays an integral role in gene expression and regulation, replication timing, and other cellular processes. Topologically associated domains (TADs), building blocks of chromosome structure, are genomic regions with higher contact frequencies within the region than outside the region. A central question is the degree to which TADs are conserved or vary between conditions. We analyze 137 Hi-C samples from 9 studies under 3 measures to quantify the effects of various sources… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Expectedly, as the data resolution becomes lower, hence, becoming less sparse, consistency of all TAD callers increased, with SpectralTAD and TopDom performing the best. Previous work using data at 100kb resolution has shown that around 60-70% of boundaries are shared between primary and replicates (Dixon et al 2012;Rao et al 2014;Sauerwald et al 2018), and our results are in agreement with these observations. In summary, these results demonstrate robust performance of SpectralTAD in detecting consistent TAD boundaries across resolutions and replicates of Hi-C data.…”
Section: Spectraltad Identifies Consistent Tads Across Resolutions Ansupporting
confidence: 93%
“…Expectedly, as the data resolution becomes lower, hence, becoming less sparse, consistency of all TAD callers increased, with SpectralTAD and TopDom performing the best. Previous work using data at 100kb resolution has shown that around 60-70% of boundaries are shared between primary and replicates (Dixon et al 2012;Rao et al 2014;Sauerwald et al 2018), and our results are in agreement with these observations. In summary, these results demonstrate robust performance of SpectralTAD in detecting consistent TAD boundaries across resolutions and replicates of Hi-C data.…”
Section: Spectraltad Identifies Consistent Tads Across Resolutions Ansupporting
confidence: 93%
“…Previous studies have shown that the overlap between TAD boundaries in replicate data ranges from around 60 to 70% (Dixon et al, 2012;Rao et al, 2014;Sauerwald et al, 2020). Additionally, technical replicates have been shown to have a slightly higher proportion of shared TAD boundaries (∼65%) than biological replicates (∼60%) (Sauerwald et al, 2020). We have tested and confirmed these observations by showing that significantly more boundaries were non-differential in technical replicates than in biological replicates (73 vs. 65.7%).…”
Section: Boundaries Are Highly Consistent In Both Technical and Biolosupporting
confidence: 60%
“…Previous studies have shown that the overlap between TAD boundaries in replicate data ranges from around 60 to 70% (Dixon et al, 2012;Rao et al, 2014;Sauerwald et al, 2020). Additionally, technical replicates have been shown to have a slightly higher proportion of shared TAD boundaries (∼65%) than biological replicates (∼60%) (Sauerwald et al, 2020).…”
Section: Boundaries Are Highly Consistent In Both Technical and Biolomentioning
confidence: 95%
See 1 more Smart Citation
“…Because of the significant involvement of cohesin in TAD formation, two protein components of cohesin, RAD21 and SMC3, have also been shown to peak around TAD boundaries [24]. While TADs have been shown to vary between single cells [28], on the population level they are expected to remain fairly consistent between replicates [20]. On a fundamental level, TADs are defined by increased contact frequency within their interiors and somewhat depleted contact frequency between different TADs.…”
mentioning
confidence: 99%